High patient satisfaction with telehealth in Parkinson disease: A randomized controlled study. Issue 3 (June 2016) - Wilkinson, Jayne R.; Spindler, Meredith; Wood, Stephanie M.; Marcus, Steven C.; Weintraub, Daniel; Morley, James F.; Stineman, Margaret G.; Duda, John E.
Abstract: Background: Parkinson disease (PD) is a complex neurodegenerative disorder that benefits from specialty care. Telehealth is an innovative resource that can enhance access to this care within a patient-centered framework. Research suggests that telehealth can lead to increased patient satisfaction, equal or better clinical outcomes, and cost savings, but these outcomes have not been well-studied in PD. Methods: We conducted a dual active-arm 12-month randomized controlled trial to assess patient satisfaction, clinical outcomes, travel burden, and health care utilization in PD using video telehealth for follow-up care with specialty providers. Telehealth visits took place either at a facility nearer to the patient (satellite clinic arm) or in the patient's home (home arm). Each control group received usual in-person care. Patient satisfaction, assessed by quantitative questionnaires, was the primary outcome. Results: Eighty-six men were enrolled (home arm: 18 active, 18 control; satellite clinic arm: 26 active, 24 control) with a mean age of 73 years (range 42–87). There were no differences in baseline characteristics between the active group and the controls in each arm ( p > 0.05). A significant difference in overall patient satisfaction was not found; however, high levels of patient satisfaction were found in all groups. Greater satisfaction for the telehealth modality was found in assessments of convenience and accessibility/distance. Clinical outcomes were similar between groups, travel burden was reduced using telehealth, and health care utilization was largely similar in both groups. Conclusions: As the need for PD subspecialty care increases, innovative patient-centered solutions to overcoming barriers to access, such as video telehealth, will be invaluable to patients and may provide high patient satisfaction.